[Article Retraction] Evaluation of an experimental rat model for comparative studies of bleaching agents - Cintra, Luciano Tavares Angelo; Benetti, Francine; Ferreira, Luciana Louzada; Rahal, Vanessa; Ervolino, Edilson; Jacinto, Rogério De Castilho; Gomes, João Eduardo; Briso, André Luiz Fraga (Faculdade De Odontologia De Bauru - USP, 2016)
Dental materials in general are tested in different animal models prior to the clinical use in humans, except for bleaching agents.
Keywords: Bleaching agents; Animal models; Hydrogen peroxide